Peran Modal Sosial Terhadap Pergeseran Sistem Nafkah Masyarakat Pasca Pembangunan Waduk Bili-Bili - Safri, Safri; Salman, Darmawan; Sakaria, Sakaria (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2026)
Large scale infrastructure development, particularly dam construction, is widely promoted as a driver of economic growth and social welfare. However, it often generates unintended socio-economic consequences at the local level. The Bili-Bili Reservoir in Gowa Regency, Indonesia, illustrates this paradox, resulting in agricultural land loss, livelihood disruption, and socio-cultural transformation, forcing communities to reconfigure their livelihood strategies under uncertainty. This study examines how social capital trust, social networks, and shared norms function as a key mechanism for sustaining livelihood resilience in post reservoir contexts. A qualitative case study was conducted in Lanna Village using in-depth interviews, participant observation, and document analysis involving 12 purposively selected informants. The findings show that social capital is central to adaptive capacity. Bonding strengthens internal solidarity; bridging expands access to economic opportunities; and linking connects communities with formal institutions and resources. These dimensions interact to enable communities not only to cope with disruption but also to reconstruct and diversify their livelihoods. This study offers a novel integrative framework linking social capital dimensions with livelihood transformation, demonstrating that social relations actively shape adaptive strategies. It concludes that adaptation depends not only on material assets but on the strength of social relations, highlighting the need to integrate social and physical infrastructure in development policy.